2009
DOI: 10.1002/rra.1318
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the health of large rivers with macroinvertebrates: Do dominant taxa help or hinder the assessment?

Abstract: Macroinvertebrate communities in the Mississippi River are often dominated by a few taxa (e.g. oligochaetes in the fine sediments and hydropsychid caddisflies on rocks) that exploit the natural abundance of fine organic particles. These taxa are moderately to highly tolerant of pollution, and the combination of high abundance and high pollution tolerance could result in the river being assessed as highly polluted. We examined how the presence or absence of dominant oligochaetes or hydropsychid caddisflies affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…An issue affecting the development of ecological indicators for large rivers is the potential for some taxa to swamp macroinvertebrate metrics based on broad taxonomic groupings (Seegert 2000). These 'swamper' taxa can include Hydropsychidae on rocks in fast-flowing sections of river (Jackson et al 2010), Oligochaeta in sections dominated by fine sediments (Battle et al 2007), and Crustacea such as the migratory shrimp Paratya and the amphipod Paracalliope which can be highly abundant in littoral habitats ; this study). Jackson et al (2010) suggested that excluding dominant taxa from metric calculations may make observed responses more comparable to wadeable stream assessments, and Seegert (2000) proposed removing interruptive species that comprised more than 50% of the catch when developing fish metrics.…”
Section: Spatial and Temporal Patternsmentioning
confidence: 97%
See 1 more Smart Citation
“…An issue affecting the development of ecological indicators for large rivers is the potential for some taxa to swamp macroinvertebrate metrics based on broad taxonomic groupings (Seegert 2000). These 'swamper' taxa can include Hydropsychidae on rocks in fast-flowing sections of river (Jackson et al 2010), Oligochaeta in sections dominated by fine sediments (Battle et al 2007), and Crustacea such as the migratory shrimp Paratya and the amphipod Paracalliope which can be highly abundant in littoral habitats ; this study). Jackson et al (2010) suggested that excluding dominant taxa from metric calculations may make observed responses more comparable to wadeable stream assessments, and Seegert (2000) proposed removing interruptive species that comprised more than 50% of the catch when developing fish metrics.…”
Section: Spatial and Temporal Patternsmentioning
confidence: 97%
“…These 'swamper' taxa can include Hydropsychidae on rocks in fast-flowing sections of river (Jackson et al 2010), Oligochaeta in sections dominated by fine sediments (Battle et al 2007), and Crustacea such as the migratory shrimp Paratya and the amphipod Paracalliope which can be highly abundant in littoral habitats ; this study). Jackson et al (2010) suggested that excluding dominant taxa from metric calculations may make observed responses more comparable to wadeable stream assessments, and Seegert (2000) proposed removing interruptive species that comprised more than 50% of the catch when developing fish metrics. We were unable to test this approach in the present study because rare taxa were not enumerated in the fixed count protocol and could not therefore be included in revised % abundance calculations, highlighting the need for full counts to provide more flexibility in the development of metrics based on large river macroinvertebrate communities.…”
Section: Spatial and Temporal Patternsmentioning
confidence: 98%
“…Although interest in investigating the biodiversity of aquatic insects in both tropical and temperate aquatic ecosystems (lentic and lotic) is growing (Murphy and Davy-Bowker 2005;Clarke et al 2008;Al-Shami et al 2010a, b, 2011Hoang et al 2010;Jackson et al 2010;Magbanua et al 2010), there is still a knowledge gap regarding the ecology and biology of tropical aquatic insects in Asian regions and their role in ecosystem stability (Morse et al 2007;Dudgeon 2008;Al-Shami et al 2010b, 2011.…”
Section: Introductionmentioning
confidence: 98%
“…Hence, they did not test ability to detect colonization of streams by invertebrate taxa as a result of taxon introductions or anthropogenic environmental changes that favor taxa not naturally present. This limitation also applies to many previous impact simulations used to evaluate bioassessment methods (Cao and Hawkins 2005, Mazor et al 2006, Cao and Epifanio 2010, Hawkins et al 2010a, Jackson et al 2010, Downie 2011, Bailey et al 2012, Snyder et al 2014), which only eliminated or changed the abundances of taxa that were initially present. However, a capacity to detect taxon additions could be important in operational bioassessment.…”
Section: Assessing Model Sensitivity With Simulated Impactsmentioning
confidence: 89%